Identification of Potentially Inappropriate Medication in Geriatric Patients at Wangaya Hospital, Denpasar City with Beers Criteria and Stopp Criteria in 2023 - Putri, Made Shinta Sanma; Prasetya, Anak Agung Ngurah Putra Riana; Kurnianta, Putu Dian Marani (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Geriatric (elderly) patients generally require a number of drugs (polypharmacy) to cure health-related conditions that tend to occur Potentially Inappropriate Medication (PIM). Identification of PIM is very important to prevent Drug Related Problems (DRP).  The purpose of the study was to identify the incidence of PIM using the Beers Criteria and STOPP Criteria and analyze the relationship between PIM risk factors and the incidence of PIM in geriatric patients at Wangaya Hospital, Denpasar City. This type of research is retrospective observational in a cross-sectional manner using simple random sampling techniques on all geriatric patients for the period 2023. Samples that met the inclusion criteria, namely geriatric patients aged ≥65 years in outpatient and inpatient facilities with geriatric patients who died and who were referred to other hospitals, were excluded from this study. Of the 354 samples, the prevalence of PIM in outpatient care was (4.23%) with the most common drugs being spironolactone (55.84%), Sulfonylureas (19.48%), and NSAIDs (6.49%) with Beers criteria. In hospitalization, (0.84%) with NSAIDs (25%), corticosteroids (25%), clopidogrel (25%), and antipsychotics (25%) with STOPP criteria. Based on the evaluation results, there was a very weak correlation between the number of drugs (p=0.000; r=0.199) and there was no relationship between the number of diagnoses (p=0.674) prescribed and the incidence of PIM. Based on this, it can be concluded that the greater the number of drugs can increase the risk of PIM.